Inflammatory Bowel Disease Patients Are Frequently Nonadherent to Scheduled Induction and Maintenance Infliximab Therapy: A Canadian Cohort Study - Christopher Ma; Chad J Evaschesen; Grenvil Gracias; Vivian W Huang; Darryl K Fedorak; Karen I Kroeker; Levinus A Dieleman; Brendan P Halloran; Richard N Fedorak (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Adherence to maintenance medication regimens in inflammatory bowel disease patients has traditionally been poor. Although infliximab has demonstrated efficacy in inducing and maintaining disease remission, adherence to regularly scheduled infliximab infusions is required to maintain therapeutic trough drug levels and prevent the development of anti-infliximab antibodies.